The influence of media use on laymen s monetary policy knowledge in Germany - Edith Neuenkirch; Bernd Hayo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyse the German citizens knowledge about monetary policy and the European Central Bank (ECB), as well as the public s use of mass communication media to obtain information about the ECB. We employ a unique representative public opinion survey of German households conducted in 2011. We find that a person s own desire to be informed about the ECB together with the use of various media channels to keep informed are decisive for both (i) the own perception of knowledge about the ECB and (ii) the actual level of knowledge. The media-related influence differs with a person s level of education and is stronger for subjective knowledge. Women are less interested and knowledgeable. We conclude that the ECB is well advised to continue its education programmes to convince the public of the importance of monetary policy literacy.
Keywords: A20; E52; E58; 330